Preparation method of carbon black dispersion for black polyimide film

By synthesizing carbon black dispersant in aprotic polar solvent, and adjusting the dispersion effect of carbon black by using the molar ratio of dianhydride monomer to diamine monomer, the problem of difficulty in dispersing carbon black and large dispersant is solved, and the problem of carbon black is achieved. High stable dispersion and excellent performance of carbon black in black polyimide film.

CN114752081BActive Publication Date: 2025-02-18SHANDONG WANDA MICROELECTRONIC MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210288109.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-23
Publication Date
2025-02-18
Estimated Expiration
2042-03-23

AI Technical Summary

Technical Problem

In the prior art, when preparing black polyimide films, it is difficult to disperse carbon black and the dispersant is used in large amounts, resulting in increased production costs and performance impacts. The high-temperature resistance of hyperbranched dispersants is poor and cannot meet the conditions of high-temperature imidation. film preparation.

Method used

By synthesizing carbon black dispersant in aprotic polar solvent, the dispersion effect of carbon black is adjusted by regulating the molar ratio (R value) of dianhydride monomer and diamine monomer, so that carbon black can be better in the polyamic acid system Dispersion to achieve uniform dispersion of carbon black in polyimide film.

Benefits of technology

It realizes high stable dispersion of carbon black in polyimide film, reduces the amount of dispersant, improves the light shielding, mechanical properties and electrical resistance of the film, and is suitable for preparation under high-temperature imidation conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114752081B_ABST
    Figure CN114752081B_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a carbon black dispersion for a black polyimide film, which is characterized in that a diamine monomer is dissolved in a strongly polar aprotic organic solvent, a dianhydride monomer is added in batches, the molar ratio of the dianhydride monomer to the diamine monomer is 0.7-0.98, the reaction temperature is 40-50°C, the reaction is carried out for 40-60 minutes, a carbon black dispersant of a polyamic acid system is obtained, the carbon black is added to the carbon black dispersant of the polyamic acid system, and the mixture is stirred and ground with a sander for 9-11 hours to obtain a carbon black dispersion. The carbon black of the application can achieve high-stability dispersion in the preparation of modified polyimide, and the stable preparation of high-performance carbon black-polyimide composite materials is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a carbon black dispersion liquid for a black polyimide film. Background Art

[0002] Polyimide (PI) is a general term for heterocyclic polymers containing imide groups in the main chain. It is one of the engineering plastics with the best heat resistance at present. It has the characteristics of radiation resistance, excellent creep resistance, excellent mechanical strength, and non-flammability. It is widely used in the fields of films, coatings, advanced composite materials, fibers, engineering plastics, etc. Polyimide can be divided into three categories: thermosetting polyimide, thermoplastic polyimide and modified polyimide, and it is developing rapidly. Among them, the composite modification of polyimide by filling to achieve the improvement of function and performance is the current research hotspot.

[0003] The preparation of aromatic polyimide by polycondensation is the current mainstream process, which is prepared by the reaction of aromatic diamine and aromatic dianhydride, aromatic tetracarboxylic acid or aromatic tetracarboxylic acid dialkyl ester. The first step is to generate polyamic acid, and the second step is to generate polyimide by thermal or chemical dehydration cyclization. The synthesis reaction of polyamic acid in the first step is the key to determining the molecular weight of polyimide, and the molecular weight of polyamic acid is usually controlled by monitoring the viscosity of the system at the end of the reaction. Since the synthesis of polycondensation polyimide is carried out in high-boiling aprotic polar solvents such as dimethylformamide (DMF), dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), etc., when filling and modifying polyimide, the modifier is usually pre-dispersed in the corresponding high-boiling aprotic polar solvent.

[0004] With the rapid development of electronic technology, higher and higher requirements are placed on its performance. Transparent yellow PI film, low thermal expansion coefficient PI film, dimensionally stable PI film, low dielectric constant PI film, black PI film, matte black PI film, matte black PI film, etc. have been developed. As an important high-temperature resistant insulating material in electronic products, polyimide is widely used in electronic devices such as flexible printed circuit boards, which play the role of isolation and insulation when combined with copper foil. Technicians have found that when using transparent light-colored PI film as a coating, the distribution of circuit design printed on the circuit layer of the circuit board can be easily interpreted and copied. Therefore, the development of high-performance opaque black PI film for use in electronic materials such as flexible circuit boards, electronic components, and lead frames of integrated circuit packages to prevent visual inspection and tampering has become a new huge market demand.

[0005] Black PI film is usually prepared by adding black coloring materials to PI film. The black coloring materials used include carbon black, carbon fiber, graphite and other carbon-based melanin, organic black dye, inorganic non-metallic oxide and other non-carbon-based melanin. Chinese Patent 1 (Application No.: 201280066713.7), Chinese Patent 2 (China Publication No. CN107987529A) and others disclose the preparation of black polyimide film using carbon black as coloring material. Japanese Patent 1 (Application No. JP2016047862A) discloses a method for preparing black polyimide film by replacing carbon black with perylene black, an organic black pigment containing a benzimidazole skeleton. Chinese Patent 3 (China Publication No. CN102260408A) discloses a method for preparing black polyimide film by using black inorganic metal oxide as melanin.

[0006] Although non-carbon black polyimide films have been reported, organic black pigments and other black colorants have many shortcomings. For example, there are few varieties of black organic pigments, poor temperature resistance, and they cannot meet the requirements of high processing temperature and durability of thermal imidization. Although inorganic black colorants do not have heat resistance problems, inorganic colorants such as metal oxides usually have high density, weak coloring ability, and are prone to sedimentation, which affects the consistency of film products. In addition, based on environmental protection requirements and environmental protection standards of relevant countries and regions, there are clear limit requirements for certain metal elements in electronic products. Therefore, carbon-based pigments, especially carbon black, are still used as the main colorants. Compared with other carbon-based pigments, carbon black has the characteristics of easy availability, low price, and strong tinting power. In addition, commercial carbon black is generally difficult to disperse, and the amount of dispersant added is too large when used (commercial dispersants are usually recommended to be used in an amount greater than 50%, relative to the mass of carbon black). The addition of excessive dispersants will bring a series of adverse effects to the production process, affecting its performance while increasing production costs.

[0007] In view of the fact that commercial carbon black is generally difficult to disperse and requires a large amount of dispersant, the inventors disclosed a black polyimide film containing a highly compatible pigment and a preparation method thereof (application number: 201911355728.5, publication number 113025038A). The invention provides a method for preparing a black pigment by utilizing a carbonizable polymer material (preferably polyimide scraps generated during production, etc.). The pigment prepared by this method has the advantages of requiring less dispersant and having good compatibility with polyimide. However, polymer materials such as carbonized polyimide increase the corresponding equipment cost, and at the same time, they also place higher demands on quality control, and have the disadvantage of low universality. Therefore, the use of commercial carbon black has the advantages of low cost, stable and controllable quality, and is the preferred pigment for preparing black polyimide materials.

[0008] The Chinese patent number is 109456481A. A method for preparing graphene oxide / polyimide is disclosed. The method comprises the following steps: adding graphene oxide to an amide solvent containing a hyperbranched dispersant, and fully dispersing the graphene oxide to obtain a graphene oxide / hyperbranched dispersant / amide solvent system; condensing and polymerizing diamine and dianhydride monomers in an amide solvent to obtain a polyamic acid solution; adding the graphene oxide / hyperbranched dispersant / amide solvent system to the polyamic acid solution under mechanical stirring, and continuously mechanically dispersing the graphene oxide in the polyamic acid solution to obtain a polyamic acid / graphene / amide solvent composite system. The problems with this method are: first, the introduced hyperbranched dispersant has poor high temperature resistance and can only meet the preparation of polyimide films with imidization temperatures below 290°C, but is not suitable for the preparation of polyimide films with higher imidization temperatures (usually above 350°C); second, the selection criteria for the dispersant are not determined according to the different pH values ​​of graphene oxide, which makes the selection of dispersants for different graphene oxides difficult and labor-intensive.

[0009] The synthesis of polyamic acid is generally obtained by adding the corresponding dianhydride to an aromatic diamine system dissolved in a high-boiling-point non-protonic polar solvent. In order to ensure the full and uniform dispersion of carbon black and the controllability of the process, the carbon black dispersion is usually added to the diamine system, at which time the system viscosity is the lowest, which is conducive to the dispersion of carbon black. With the addition of dianhydride, the properties of the system change to a great extent, and it becomes particularly important to ensure the stable dispersion of carbon black throughout the production process.

[0010] In practice, the applicant has found that carbon black can be well dispersed in high-boiling-point non-protonic polar solvents (such as DMAc, etc.) by selecting commercial dispersants. However, there are many difficulties in achieving stable dispersion of carbon black in the synthesis process of black polyimide. Common problems include: when a well-dispersed carbon black dispersion is added to a diamine solution, poor dispersion such as flocculation occurs; a well-dispersed carbon black dispersion system in a diamine solution is also prone to deterioration of dispersion conditions during the preparation of polyamic acid by adding dianhydride. The existence of the above problems leads to a narrower range of dispersants and increased difficulty in preparing carbon black dispersions. In addition, there are many varieties of carbon black on the market. In terms of tinting power, carbon black can be divided into three categories: high-pigment carbon black, medium-pigment carbon black and low-pigment carbon black. In terms of the structure of carbon black, it can be divided into high-structure carbon black, medium (standard) structure carbon black and low-structure carbon black.

[0011] Therefore, in view of the high requirements and difficulty in preparing carbon black dispersions for black polyimide films, the main purpose of the present invention is to seek a technology for achieving highly stable dispersion of carbon black in the preparation of modified polyimide and to achieve stable preparation of high-performance carbon black-polyimide composite materials. Summary of the invention

[0012] The invention provides a method for preparing a carbon black dispersion for a black polyimide film, and solves a technical problem of providing a carbon black dispersion technology and method for preparing a black polyimide film. The method uses monomers of dianhydride and diamine to synthesize a carbon black dispersant in a non-protonic polar solvent. The dispersant can adjust the dispersing effect of the carbon black in the dispersion by adjusting the molar ratio of the dianhydride monomer to the diamine monomer according to the different pH values ​​of the dispersed carbon black. The dispersant of the carbon black dispersion prepared by the method is consistent with the polyamic acid system for preparing the polyimide film, so the carbon black dispersion can be better dispersed in the polyamic acid for preparing the polyimide film, thereby achieving uniform dispersion of the carbon black in the polyimide film.

[0013] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0014] A method for preparing a carbon black dispersion for a black polyimide film is carried out according to the following steps:

[0015] 1) Preparation of a carbon black dispersant of a polyamic acid system: dissolving a diamine monomer in a strongly polar aprotic organic solvent, adding a dianhydride monomer in batches, wherein the molar ratio of the dianhydride monomer to the diamine monomer is 0.7 to 0.98, the reaction temperature is 40 to 50° C., and the reaction time is 40 to 60 minutes to obtain a carbon black dispersant of a polyamic acid system;

[0016] 2) Preparation of carbon black dispersion: adding carbon black to the carbon black dispersant of the polyamic acid system, stirring and grinding for 2 to 11 hours to obtain the carbon black dispersion;

[0017] The mass ratio of the used diamine monomer weight to the strongly polar aprotic organic solvent is 1:10-1000; the mass ratio of the carbon black to the carbon black dispersant of the polyamic acid system is 1:4-80.

[0018] The diamine monomer is one or more of phenylenediamine and diaminodiphenyl ether or their derivatives; the dianhydride monomer is one or more of biphenylcarboxylic acid dianhydride or its derivatives and pyromellitic acid dianhydride or its derivatives; the highly polar aprotic organic solvent is one or more of DMF, DMAc, DMSO and NMP;

[0019] The DMF is N,N-dimethylformamide; the DMAc is N,N-dimethylacetamide; the DMSO is dimethyl sulfoxide; and the NMP is N-methylpyrrolidone.

[0020] The diamine monomer is one or more of p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, 3,4-diaminodiphenyl ether, 2,4-diaminodiphenyl ether and 4,4'-diaminodiphenyl ether; the dianhydride monomer is one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and p-phenylene-bis-trimellitic dianhydride.

[0021] The batch addition is to add the dianhydride monomer in two times, the first addition amount is 30%-60% of the molar amount of the diamine monomer, and the sum of the second addition amount and the first addition amount is 70%-98% of the molar amount of the diamine monomer.

[0022] The molar ratio of dianhydride monomer to diamine monomer is determined by the properties of carbon black;

[0023] When the carbon black is acidic or neutral, the molar ratio of the dianhydride monomer to the diamine monomer is 0.7 to 0.9;

[0024] When the carbon black is alkaline, the molar ratio of the dianhydride monomer to the diamine monomer is 0.9 to 0.98;

[0025] The acidic or neutral refers to a pH value of 2.5 to 7.5;

[0026] The alkalinity refers to a pH value of 7.5 to 9.5.

[0027] The grinding in step 2) is divided into grinding with a sander and grinding with a high-energy ball mill;

[0028] The grinding conditions of the sander are a rotation speed of 2800 r / min and a time of 9 to 11 h;

[0029] The grinding conditions of the high energy ball mill are a rotation speed of 800 r / min and a grinding time of 2 to 5 h.

[0030] The inventors used pyromellitic dianhydride (PMDA) and 4,4-diaminodiphenyl ether (ODA) as typical raw materials to prepare

[0031] The process of polyimide is analyzed. It shows the process of using PMDA and ODA as starting materials to synthesize polyamic acid and generate polyimide through thermal cyclization.

[0032]

[0033] The process of PMDA and ODA reacting to form polyimide (1 is the formation of polyamic acid, 2 is the thermal cyclization to form polyimide)

[0034] The invention has the following beneficial technical effects:

[0035] 1. In the process of adding dianhydride raw materials to diamine solution to form polyamic acid, there is a process in which the amino group is reduced due to the reaction and the carboxyl group and acyl group are generated. At the same time, as the molecular weight of the polyamic acid increases, the viscosity of the system is also increasing. The three types of groups mentioned above are active groups that can achieve anchoring on the surface of carbon black and then achieve dispersion of carbon black.

[0036] 2. The main control parameters of the synthesis process of polyamic acid are the concentration of diamine dissolved in the high boiling point aprotic polar solvent (hereinafter represented by P) and the molar ratio of the added dianhydride to diamine (hereinafter represented by R).

[0037] The applicant has found that among these two parameters, the R value is the key control parameter, and there is no particularly strict requirement for the P value, which is limited to the solubility of the diamine selected in the selected solvent.

[0038] Furthermore, preferably, when synthesizing a carbon black dispersant by reacting dianhydride with a dissolved diamine, the P value is selected to be the solubility value of the diamine in the selected solvent at room temperature, or slightly lower than this value. In this case, the concentration of the synthesized carbon black dispersant is higher, the amount required for processing is less, and it is convenient for storage and subsequent operations.

[0039] The applicant has noticed in practice that the selection of R value is the key to achieve stable dispersion of carbon black. A large number of experiments have shown that the selection of R value is mainly related to the pH value of the commercial carbon black used.

[0040] Through the investigation of the mainstream commodity carbon black in the market, it is found that more than 95% of the carbon black is currently produced by the oil furnace method. The pH value of general furnace carbon black is usually greater than 7, which is slightly alkaline. Through surface modification, the alkalinity can be neutralized and its pH value can be adjusted to neutral or acidic. The pH value of commercial carbon black is mostly in the range of 2~10.

[0041] By sampling the products of Orion, a world-renowned carbon black manufacturer, representative pH samples were selected for different R value dispersant tests. In order to make the experiments comparable, the mass percentage of carbon black was kept at 20% during the experiment. The mass of the introduced diamine was 30% of the mass of carbon black and was pre-dissolved in the required high-boiling point aprotic polar solvent. According to the different R values, the corresponding mass of dianhydride was weighed and added to the solution in batches during stirring to obtain the experimental carbon black dispersion carrier. The required carbon black was added to the above polyamic acid solution, and the dispersion effect was evaluated after sand grinding. The selected carbon black is shown in Table 1 below.

[0042] Table 1 List of carbon black samples used in the experiment

[0043]

[0044] After analyzing and sorting out a large amount of test data, the corresponding relationship between carbon black pH value and R was established based on the evaluation of carbon black dispersion effect.

[0045] Acidic carbon black has a lower R value (R value is 0.7~0.9), and there are more amino groups in the dispersed system that do not participate in the polyamic acid synthesis reaction; while for alkaline carbon black, a higher R value (R value is 0.9~0.98) is conducive to the dispersion of carbon black.

[0046] It should be noted that the present invention provides a technical solution for dispersing carbon black for polyimide film. Due to the large variety of carbon black, the optimal R value and the amount of dispersant used need to be determined according to the actual conditions.

[0047] The applicant conducted similar experiments on other brands of carbon black and found that the above R value selection and the dependence on the pH value of carbon black are established. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a relationship diagram between the pH value and R value of carbon black established based on the evaluation of dispersion effect;

[0049] Figure 2 This is a scanning electron microscope (SEM) image of the polyimide film sample prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0050] The present invention is further described below with reference to specific examples.

[0051] Example 1

[0052] Experimental raw materials: N,N-dimethylacetamide (DMAc), pyromellitic dianhydride (PMDA), 4,4'-diaminodiphenyl ether (ODA), carbon black (brand: Orion FW200; pH value 2.5);

[0053] Experimental equipment: double-layer glass reactor, circulating cooler, electric stirrer, sand mill;

[0054] Add 695g DMAc to a double-layer glass reactor, add 60g ODA, start the electric stirrer and stir at 150r / min for 30min, divide 45g PMDA into two equal parts, slowly add the first part of dianhydride to the reactor and stir for 15min. Then slowly add the second part of dianhydride to the reactor and stir for 30min. During the reaction, the polymerization temperature is controlled between 45±2℃. Add 200g carbon black (brand: Orion FW200, pH value is 2.5) and stir evenly. Then grind the slurry with a sand mill at 2800r / min for 10 hours.

[0055] The mass percentage of carbon black in the obtained dispersion was 20%, the molar ratio of PDMA to ODA was 0.7 (R=0.7), and the initial concentration of ODA was 7.5%.

[0056] The median particle size of the carbon black in the prepared carbon black dispersion was 50 nm (D 50 =50nm), no sedimentation within 90 days.

[0057] Embodiment 2:

[0058] The technical solutions adopted in this embodiment are similar to those in Example 1, except that the carbon black brand adopted is LampBLACK 101 (the commercial pH value is 7.5), and the mass of PDMA adopted is 58.81 g (at this time, R=0.9).

[0059] The median particle size of the carbon black in the prepared carbon black dispersion was 50 nm (D 50 =50nm) for 90 days: no sedimentation.

[0060] Example 3: Preparation of carbon black dispersion for black polyimide film

[0061] The technical solutions adopted in this embodiment are similar to those in Example 1, except that the carbon black grade adopted is PRINTEX L6 (the commercial pH value is 9.5), and the mass of PDMA adopted is 64 g (at this time, R is 0.98).

[0062] The median particle size of the carbon black in the prepared carbon black dispersion was 50 nm (D 50 =50nm), and there was no sedimentation after 90 days.

[0063] Example 4: Preparation of black polyimide film

[0064] Experimental raw materials: N, N-dimethylacetamide (DMAc), pyromellitic dianhydride (PMDA), 4,4'-diaminodiphenyl ether (ODA), carbon black (brand: Orion FW200, pH value 2.5) dispersion prepared in Example 1;

[0065] Experimental equipment: double-layer glass reactor, circulating cooler, electric stirrer

[0066] The mass percentage of carbon black in the prepared black polyimide film is about 5%, and the solid content in the polyamic acid preparation system is about 20%. 40g DMAc and 4.786g ODA are added to a double-layer glass reactor, and an electric stirrer is started to stir for 30 minutes at a speed of 150r / min. Under stirring, 2.5g of the carbon black dispersion prepared in Example 1 is added to the solution. 98% of PMDA in an equal molar amount (5.214g) as ODA is evenly divided into two parts, and the first part of dianhydride is slowly added to the reactor, stirred for 15 minutes, and then the second part of dianhydride is slowly added to the reactor and stirred for 30 minutes. The remaining 2% ODA molar amount of dianhydride is used to adjust the resin viscosity, and its value is controlled between 40-50pa.s. The temperature is controlled at 45±2℃ during the reaction. The obtained resin liquid is degassed under vacuum conditions for 10 hours to obtain a clear polyamic acid resin solution;

[0067] Clean the glass plate, apply the obtained resin evenly with an 80μm wire rod, and after 5 minutes of leveling, put it in a 120℃ oven to remove the solvent for 20 minutes. Take it out and cool it down, then peel off the obtained resin film. Fix it with a clamp around it and put it into an electric furnace for thermal imidization. The imidization temperature system is to uniformly increase the temperature from room temperature to 400℃ within 30 minutes, keep it warm for 2 minutes, and then take it out to obtain a black polyimide film.

[0068] The scanning electron microscope photos of the prepared film samples are shown in the attached Figure 1 As shown, it shows that the carbon black has no obvious agglomeration and is evenly dispersed in the polyimide matrix. After testing, the thickness of the prepared polyimide film is about 13μm, the transmittance (380nm~780nm) is less than 0.5% at all wavelengths, the tensile strength is 180MPa, the elongation at break is 31%, and the electrical strength is 165KV / mm. The excellent light-shielding, mechanical and electrical properties indicate the good dispersion uniformity of carbon black and its excellent bonding with the matrix.

[0069] Example 5: Preparation of black polyimide film

[0070] Experimental raw materials: N,N-dimethylacetamide (DMAc), pyromellitic dianhydride (PMDA), 4,4'-diaminodiphenyl ether (ODA), carbon black (brand: Orion PRINTEX L6, pH 9.5);

[0071] Experimental equipment: double-layer glass reactor, circulating cooler, electric stirrer, high-energy ball mill

[0072] Preparation of carbon black dispersion: Add 50g DMAc to a glass beaker, add 0.108g ODA, start an electric stirrer and stir at 150r / min for 30 minutes, then add 0.115g PDMA (the molar ratio R of PDMA to ODA is 0.98 at this time), and after the reaction is complete and the solution is transparent, add 0.625g carbon black (brand: Orion PRINTEX L6) and stir evenly. Pour the resulting liquid into a 100ml high-energy ball mill, add 20g yttrium-stabilized zirconia grinding balls with a diameter of 0.3mm, and sand mill for 2h at a speed of 800rpm, with 1min in each forward and reverse directions, to obtain a black dispersion. The particle size is 50 nm (D50) as measured by a laser particle size analyzer.

[0073] Preparation of black slurry: The mass percentage of carbon black in the prepared black polyimide film is about 5%, and the solid content in the polyamic acid preparation system is about 20%. Add 40g of the dispersion after high-energy ball milling to the double-layer glass reactor, add 4.786g ODA, start the electric stirrer and stir at 150r / min for 30 minutes, divide 98% of the PMDA in the same molar amount as ODA (5.214g) into two parts, slowly add the first part of dianhydride to the reactor and stir for 15min. Then slowly add the second part of dianhydride to the reactor and stir for 30min. The remaining 2% ODA molar amount of dianhydride is used to adjust the resin viscosity, and its value is controlled between 40-50pa.s. The temperature is controlled at 45±2℃ during the reaction. Degas the obtained resin liquid under vacuum conditions for 10h to obtain a clear polyamic acid resin solution;

[0074] Preparation of black polyimide film: Clean the glass plate, evenly coat the obtained resin with an 80μm wire rod, and after 5 minutes of leveling, put it in a 120℃ oven to remove the solvent for 20 minutes. Take it out and cool it down, then peel off the obtained resin film. Fix it with a clamp around it and put it into an electric furnace for thermal imidization. The imidization temperature system is to uniformly increase the temperature from room temperature to 400℃ within 30 minutes, keep it warm for 2 minutes, and then take it out to obtain a black polyimide film.

[0075] After testing, the prepared polyimide film has a thickness of about 13μm, a transmittance (380nm~780nm) of less than 0.5% at all wavelengths, a tensile strength of 178MPa, an elongation at break of 33%, and a dielectric strength of 160KV / mm.

[0076] Comparative Example 1

[0077] Experimental raw materials: N, N-dimethylacetamide (DMAc), pyromellitic anhydride (PMDA), 4,4'-diaminodiphenyl ether (ODA), carbon black (brand: Orion FW200, pH value 2.5), dispersant is German Merck MOK-5032;

[0078] Experimental equipment: double-layer glass reactor, circulating cooler, electric stirrer, high-energy ball mill

[0079] Preparation of black slurry: The selected high-pigment carbon black is German Orion Carbon Black FW200, and the dispersant is German Merck MOK-5032. In this comparative example, a high-energy ball mill was used to conduct an experiment on the effect of different dispersant addition amounts on the dispersion effect of carbon black, and the results are listed in Table 2 below. The results show that when the dispersant amount is less than 20% of the carbon black mass fraction, the dispersion effect is very poor, and the carbon black agglomerates seriously. The amount of dispersant required to achieve a good dispersion effect is more than 70%.

[0080] Table 2 shows the effect of different dispersant addition amounts on carbon black dispersion

[0081]

[0082] Preparation of black polyimide film: The method for preparing the polyimide film is basically the same as that in Example 4, except that the carbon black dispersion used in this example is prepared by adding 70% of the carbon black solid amount of German Merck MOK-5032 dispersant and high-energy ball milling. The other steps are the same as in Example 4.

[0083] After testing: the film thickness is about 12.5μm, the light transmittance (380nm~780nm) is up to 7.3%, which is greatly improved and the light shielding property is greatly reduced compared with Example 4. The tensile strength is 120MPa, the elongation at break is 21%, and the electrical strength is 60KV / mm. Under similar conditions, all performance indicators are greatly reduced compared with Example 4.

[0084] Comparative Example 2

[0085] Experimental raw materials: N, N-dimethylacetamide (DMAc), pyromellitic anhydride (PMDA), 4,4'-diaminodiphenyl ether (ODA), carbon black (brand: Orion FW200, pH value 2.5), dispersant is Silok Dispers 7455;

[0086] Experimental equipment: double-layer glass reactor, circulating cooler, electric stirrer, high-energy ball mill

[0087] Preparation of black slurry: The selected high-pigment carbon black is German Orion Carbon Black FW200, and the dispersant is German Merck Silok Dispers7455. In this comparative example, a high-energy ball mill was used to conduct an experiment on the effect of different dispersant addition amounts on the dispersion effect of carbon black, and the results are listed in Table 2 below. The results show that when the dispersant amount is less than 15% by mass fraction of carbon black, the dispersion effect is very poor, and the carbon black agglomerates seriously. The amount of dispersant required to achieve a good dispersion effect is more than 50%.

[0088] Table 3 shows the effect of different dispersant addition amounts on carbon black dispersion

[0089]

[0090] Preparation of black polyimide film: The method for preparing the polyimide film is basically the same as that in Example 4, except that the carbon black dispersion used in this example is prepared by adding Silok Dispers 7455 with 50% of the carbon black solid content and high-energy ball milling. The other steps are the same as those in Example 4.

[0091] After testing: the film thickness is about 12.5μm, the light transmittance (380nm~780nm) is up to 5.8%, which is greatly improved and the light shielding property is greatly reduced compared with Example 4. The tensile strength is 115MPa, the elongation at break is 27%, and the electrical strength is 45KV / mm. Under similar conditions, all performance indicators are greatly reduced compared with Example 4.

[0092] Comparative Example 2: 1: Table 3 shows that the dispersion effect of the hyperbranched dispersant can only reach 61nm, which is worse than the dispersion effect of 50nm of the synthetic dispersion of this patent.

[0093] 2: Preparation effect of black polyimide film Under the same conditions as in Example 4 (imidization at 400°C), the properties of the prepared black polyimide film are poor, indicating that it is not suitable for the preparation of black polyimide film under high-temperature imidization conditions of 400°C.

[0094] Comparative Example 3

[0095] Experimental raw materials: N,N-dimethylacetamide (DMAc), pyromellitic dianhydride (PMDA), 4,4'-diaminodiphenyl ether (ODA), carbon black (brand: Orion FW200; pH value 2.5);

[0096] Experimental equipment: double-layer glass reactor, circulating cooler, electric stirrer, sand mill;

[0097] Preparation of carbon black dispersion: Add 695g DMAc and 60g ODA to a double-layer glass reactor. Start the electric stirrer and stir at 150r / min for 30min. Divide 62.09g (R=0.95) PMDA into two equal parts, slowly add the first part of dianhydride to the reactor and stir for 10-15min. Then slowly add the second part of dianhydride to the reactor and stir for 30min. The temperature is controlled at 40-50℃ during the reaction. Add 200g carbon black (brand: Orion FW200, pH value is 2.5) and stir evenly. Grind the slurry with a sand mill for 10 hours.

[0098] Preparation of black slurry: The preparation method is basically the same as the preparation method of black slurry in Example 4, except that in this example, R=0.95 carbon black dispersion is selected instead of R=0.7 carbon black dispersion. The other steps are the same as in Example 4.

[0099] Preparation of black polyimide film: The method for preparing the polyimide film is basically the same as that in Example 4, except that in this example, the carbon black dispersion with R=0.95 is substituted for the carbon black dispersion with R=0.7. The other steps are the same as those in Example 4.

[0100] After testing: the film thickness is about 12.5μm, the light transmittance (380nm~780nm) is up to 5.3%, which is significantly increased and the light shielding property is significantly reduced compared with Example 4. The tensile strength is 133MPa, the elongation at break is 23%, and the electrical strength is 70KV / mm. Under similar conditions, all performance indicators are significantly reduced compared with Example 4.

[0101] Comparative Example 4

[0102] Experimental raw materials: N,N-dimethylacetamide (DMAc), pyromellitic dianhydride (PMDA), 4,4'-diaminodiphenyl ether (ODA), carbon black (brand: Orion PRINTEX L6, pH value 9.5);

[0103] Experimental equipment: double-layer glass reactor, circulating cooler, electric stirrer, high-energy ball mill

[0104] Preparation of carbon black dispersion: Add 50g DMAc to a glass beaker, add 0.108g ODA, start an electric stirrer and stir at 150r / min for 30min, then add 0.088g PDMA (the molar ratio R of PDMA to ODA is 0.75 at this time), and after the reaction is complete and the solution is transparent, add 0.625g carbon black (brand: Orion PRINTEX L6) and stir evenly. Pour the resulting liquid into a 100ml high-energy ball mill, add 20g yttrium-stabilized zirconia grinding balls with a diameter of 0.3mm, and grind for 2h at 800rpm, with 1min of sand exchange in the forward and reverse directions, to obtain a carbon black dispersion.

[0105] Preparation of black slurry: The preparation method is basically the same as the preparation method of black slurry in Example 5, except that in this example, R=0.75 carbon black dispersion is selected instead of R=0.98 carbon black dispersion. The other steps are the same as in Example 5.

[0106] Preparation of black polyimide film: The method for preparing the polyimide film is basically the same as that in Example 5, except that in this example, the carbon black dispersion with R=0.75 is substituted for the carbon black dispersion with R=0.98. The other steps are the same as those in Example 5.

[0107] After testing: the film thickness is about 12.5μm, the light transmittance (380nm~780nm) is up to 5.8%, which is significantly increased and the light shielding property is significantly reduced compared with Example 5. The tensile strength is 128MPa, the elongation at break is 27%, and the electrical strength is 83KV / mm. Under similar conditions, all performance indicators are significantly reduced compared with Example 5.

[0108] From the data comparison between Comparative Example 3 and Example 4 and between Comparative Example 4 and Example 5, it can be seen that different acidity of carbon black and different molar ratios of dianhydride to diamine in the corresponding dispersion can achieve better dispersion effect.

Claims

1. A method for preparing a carbon black dispersion for a black polyimide film, characterized in that: Follow the steps below to proceed 1) Preparation of a carbon black dispersant of a polyamic acid system: dissolving a diamine monomer in a strongly polar aprotic organic solvent, adding a dianhydride monomer in batches, wherein the molar ratio of the dianhydride monomer to the diamine monomer is 0.7 to 0.98, the reaction temperature is 40 to 50° C., and the reaction time is 40 to 60 minutes to obtain a carbon black dispersant of a polyamic acid system; 2) Preparation of carbon black dispersion: adding carbon black to the carbon black dispersant of the polyamic acid system, stirring and grinding for 2 to 11 hours to obtain the carbon black dispersion; The mass ratio of the used diamine monomer weight to the strongly polar aprotic organic solvent is 1:10-1000; the mass ratio of the carbon black to the carbon black dispersant of the polyamic acid system is 1:4-80; The molar ratio of dianhydride monomer to diamine monomer is determined by the properties of carbon black; When the carbon black is acidic or neutral, the molar ratio of the dianhydride monomer to the diamine monomer is 0.7 to 0.9; When the carbon black is alkaline, the molar ratio of the dianhydride monomer to the diamine monomer is 0.9 to 0.98; The acidic or neutral refers to a pH value of 2.5 to 7.5; The alkalinity refers to a pH value of 7.5 to 9.

5.

2. The method for preparing a carbon black dispersion for a black polyimide film according to claim 1, wherein: The diamine monomer is one or more of phenylenediamine and diaminodiphenyl ether or their derivatives; the dianhydride monomer is one or more of biphenylcarboxylic acid dianhydride or its derivatives and pyromellitic acid dianhydride or its derivatives; the highly polar aprotic organic solvent is one or more of DMF, DMAc, DMSO and NMP; The DMF is N,N-dimethylformamide; the DMAc is N,N-dimethylacetamide; the DMSO is dimethyl sulfoxide; and the NMP is N-methylpyrrolidone.

3. The method for preparing a carbon black dispersion for a black polyimide film according to claim 2, wherein: The diamine monomer is one or more of p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, 3,4-diaminodiphenyl ether, 2,4-diaminodiphenyl ether and 4,4'-diaminodiphenyl ether; the dianhydride monomer is one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and p-phenylene-bis-trimellitic dianhydride.

4. The method for preparing a carbon black dispersion for a black polyimide film according to claim 1, wherein: The batch addition is to add the dianhydride monomer in two times, the first addition amount is 30%-60% of the molar amount of the diamine monomer, and the sum of the second addition amount and the first addition amount is 70%-98% of the molar amount of the diamine monomer.

5. The method for preparing a carbon black dispersion for a black polyimide film according to claim 1, characterized in that: The grinding in step 2) is divided into grinding with a sander and grinding with a high-energy ball mill; The grinding conditions of the sander are a rotation speed of 2800 r / min and a time of 9 to 11 h; The grinding conditions of the high energy ball mill are a rotation speed of 800 r / min and a grinding time of 2 to 5 h.

Citation Information

Patent Citations

  • Black polyimide film and copper foil laminate containing the film

    CN102260408A

  • Black polyimide film

    CN104169330B

  • Preparation method of matte black polyimide thin film

    CN107987529A

  • Preparation method of graphene oxide / polyimide black film

    CN109456481A

  • A black polyimide film containing a highly compatible pigment and its preparation method

    CN113025038B